2016
DOI: 10.1051/matecconf/20178702003
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption Analysis Based on Energy Efficiency Approach: A Case of Suburban Area

Abstract: Abstract. Sufficient data about electricity consumption over large periods of time was accumulated and analysed in order to develop appropriate electricity-saving measures. An important first step was to analyse and identify electrical appliances that had energy saving potential. Different behavioural consumption profiles were analysed using information from two sources: 1) technical data about electricity consumption (electricity bill) and 2) data about household electrical appliance usage and consumer awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…According to [9], the energy consumption of the housing industry is an significant component of the complete demand for electricity. Buildings as designed today, due to excessive power usage, lead to severe environmental issues [10].…”
Section: Energy Consumptionmentioning
confidence: 99%
“…According to [9], the energy consumption of the housing industry is an significant component of the complete demand for electricity. Buildings as designed today, due to excessive power usage, lead to severe environmental issues [10].…”
Section: Energy Consumptionmentioning
confidence: 99%
“…According to Rahman et al, (2017) electricity can be saved through conserving or improving efficiency of energy. Conserving energy means performing fewer activities that use electricity.…”
Section: Problem Statementmentioning
confidence: 99%
“…As explained by Energy Commission (2014), the star rating ranges from 2-star to 5-star, with 2-star explaining minimal efficiency and 5-star representing maximum efficiency. Despite of this effort, the awareness level among residential sector towards energy efficiency is still low (Rahman et al, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to approach the problem with both technical efficiency improvements and behaviour change through raising awareness on energy-saving practices. Rahman, et al (2017) reported that many people in Malaysia did not know how to increase energy efficiency in their daily energy use. Strategies for increasing energy efficiency in buildings can become ineffective due to residents' energy consumption behaviour (Hussaini & Abdul Majid, 2015).…”
Section: Introductionmentioning
confidence: 99%